Kebijakan Hukum Pidana Terhadap Bukti Elektronik: Antara Eksistensi, Hambatan Penggunaan, dan Urgensi Pengaturannya Dalam Kitab Undang-Undang Hukum Acara Pidana - Cantika, Gebby; Yunara, Edi; Trisna, Wessy (Talenta Publisher, Universitas Sumatera Utara, 2025)
The rapid development of technology has resulted in the Criminal Procedure Code (KUHAP) not being able to accommodate criminal acts related to technology. In response to these conditions, the government issued Law Number 11 of 2008 concerning Electronic Information and Transactions which introduced electronic evidence as legal evidence. This recognition is also found in other special laws. However, scattered confessions have created uncertainty regarding the legal position of electronic evidence in the criminal justice system. As a result, the use of electronic evidence is less than optimal in the process of proving and resolving criminal cases. The purpose of this paper is to analyze the existence of electronic evidence as a valid form of evidence in Indonesia, then to identify obstacles to the use of electronic evidence in criminal justice in Indonesia and examine the urgency of regulating electronic evidence as a criminal law policy in criminal justice in Indonesia. The research method in this journal is normative legal research with a statutory regulation approach, comparative approach, case approach and historical approach.. The author uses secondary data sources consisting of primary legal materials, secondary legal materials and tertiary legal materials. Data collection techniques were carried out through literature study, then analyzed qualitatively. This research examines the position of electronic evidence in various special laws and its application in court decisions, then identifies obstacles related to procedures, understanding of law enforcement officials, and limited infrastructure, as well as explaining the urgency of ratifying the draft criminal procedure code (RKUHAP) to strengthen the legal basis for electronic evidence. The results of this research show that electronic evidence needs to be regulated in Indonesian criminal procedural law through updating the Criminal Procedure Code in order to provide legal certainty and facilitate the use of electronic evidence in Indonesian criminal procedural law.